Análise dos acidentes de trânsito envolvendo motocicletas em rodovias concessionadas no sul do Brasil - Breda, Glaucia Ritter (2015)
The study aimed to describe the epidemiological profile of accidents involving motorcycles in concession highways in the state of Paraná. This is an observational cross-sectional study using secondary data that were collected from the concessionaire itself accident reports. It was found that between January 1 2011 and December 31 2013, there were 1056 accidents involving 1322 people, predominantly male and aged between 18 and 29 years. Most suffered minor injuries. Of those who suffered serious injuries or died at the scene, most were male, with association between the degree of injury and sex of those involved. The highest number of accidents concentrated on BRs 369 and 376, but it was the PR 317 with the highest death rate from accidents. Almost half of the accidents resulted from motorcycle fall, and in most cases, drivers had accidents alone. Analyzing the outcome of death, most occurred in good weather conditions, normal traffic, dry track and double, but with reduced visibility. Knowing the factors associated with these events on highways, allowed us to outline the profile of these, which differs from occurring in urban environments. Different interventions should therefore be adopted, reducing accident rates involving bikers in the country.